Inhibition of Epac2 Attenuates Neural Cell Apoptosis and Improves Neurological Deficits in a Rat Model of Traumatic Brain Injury - Zhang, Ling; Zhang, Li; Liu, Huixiang; Jiang, Feng; Wang, Huanjing; Li, Di; Gao, Rong (Frontiers in Neuroscience, 2018)
Traumatic brain injury (TBI) is a major cause of mortality and disability worldwide. TBI-induced neuronal apoptosis is one of the main contributors to the secondary injury process. The aim of this study is to investigate the involvement of Exchange protein directly activated by cAMP 2 (Epac2) on TBI. We found that the expression level of Epac2 surrounding the injured area of brain in rats of TBI model was significantly increased at 12h after TBI. The role of Epac2 in TBI was further explored by using a selective Epac2 antagonist ESI-05 to decrease the Epac2 expression. We discovered that inhibition of Epac2 could improve the neurological impairment and attenuate brain edema following TBI. The Epac2 inhibition effectively reduced neuronal cell death and P38 MAPK signaling pathway may be involved in this process. Our results suggest that inhibition of Epac2 may be a potential therapy for TBI by reducing the neural cell death, alleviating brain edema and improving neurologic deficits.